Khawarij and Murji'ah in the Perspective of Contemporary Islamic Thought: Relevance and Challenges in the Modern Era - Abdul Husain Natsir; Nurlaelah Abbas (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the thought of Khawarij and Murji'ah in contemporary Islamic context with a focus on the relevance and application of these historical theological concepts to issues of extremism and moderation in the modern era. Through a qualitative approach with library research method, this study analyzes the doctrines of both groups and contemporary manifestations of their thinking. The results show that contemporary religious extremism phenomena have ideological connections with classical Khawarij characteristics such as takfirism, textual literalism, and tendency toward violence, while excessive political apathy reflects similarities with Murji'ah. The main challenges identified are how to balance religious commitment with tolerance in plural societies, and to overcome extreme tendencies in religious interpretation. In conclusion, a deep understanding of the historical roots of this thought can contribute to the development of a comprehensive approach to religious moderation in the modern era, with significant implications for social harmony and deradicalization efforts.